PENGARUH FAKTOR FUNDAMENTAL DALAM PENENTUAN KEBIJAKAN PEMBAYARAN DIVIDEN PADA PERUSAHAAN PABRIKAN - Alia Ariesanti (Universitas Ahmad Dahlan, 2012)
The aim of this study is to analyze the effect of liquidity, profitability, solvability, and history of dividend-payment on dividend policy. This study focused on sample manufacturing firms, that shared dividend between 2007-2011 or not shared which listing in Indonesia Stock Exchange. To analyze the relationship, this study used logistic regression because the measurement of dependend variable is binary. This study found an empirical prove that history of dividen-payment impacted on dividend policy. The possibility of dividend-payment by company had history one year ahead dividend-payment greater 64 times than company that not paid. The another independend variables, that is liquidity, profitability, and solvability, not impacted on dividend policy. Signalling devidend theory provided the answer to explain this result study.